Comparative Evaluation of effect of resin protective coatings on the surface hardness and shear punch strength of different GlCs - An InVitro Study - N. Mishra; M. Agarwal; M. P. Singh; A. Khullar; K. Magwa; S. S. Thakur (Эндодонтия Today)
G-Coat Plus is a nano-filled, self-adhesive light cured protective coating that strengthens, protects and enhances glass ionomer restorations. The effect of G- Coat plus on different GICs have not been studied comprehensively. Hence the study was conducted to compare the effect of resin coating on surface hardness and Shear punch strength of newer modified GIC.Materials and methods: 120 samples of three GICs i.e. Fuji IX Extra, Fuji IX Fast, Fuji II LC were prepared using specialized metal moulds. Specimens of Fuji II LC were light cured for 20 seconds. Coated and uncoated samples were tested for surface hardness and 30 samples were tested for shear punch strength. P < 0.05 was considered as significant. Results: Shear Punch Strength after G-Coat plus coating was significantly higher for Fuji IX Extra followed by Fuji II LC. Surface Hardness after G- Coat plus coating was significantly higher for Fuji IX Extra followed by Fuji IX Fast and Fuji II LC.Conclusion: Surface coating by a resin agent significantly increases the surface hardness and shear strength of the GIC. Considering the above stated findings, they can be incorporated into daily clinical practice to enhance the strength and longevity of GIC.